Phytochemical and In-Vitro Antioxidant Activity of Ethanolic Extract of Strobilanthes Barbatus Nees Leaves - SUBBULEKSHMI, K. O.; GODWIN, S. E.; VAHAB, A. ABDUL (Asian Journal of Pharmaceutical Research and Development, 2015)
Overproduction of oxidants in certain conditions may cause oxidative stress leading to oxidative damage to biomolecules and cells. Hence natural antioxidants are virtually important for human health. The ethanolic extract of Strobilanthes barbatus(EESB) leaves were evaluated for phytochemical tests and in-vitro antioxidant activity against DPPH(1,1-diphenyl2-picrylhydrazyl)radical,superoxide radical and hydroxyl radical scavenging activity. The results of phytochemical tests revealed the presence of carbohydrates, alkaloids,phenolics, tannins,flavonoids, steroids and triterpenoids. The results of invitro antioxidant activity revealed that concentrations of the plant extracts required for 50% inhibition of DPPH radical scavenging effect (IC50) were recorded as15μg/ml, Superoxide radical scavenging activity IC50 value of 250μg/ml and hydroxyl radical scavengingIC50 value of 525μg/ml as compared with standard drug ascorbic acid.